2020
DOI: 10.1101/2020.12.25.20248859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public adherence to precautionary measures and preventive guidelines against COVID-19 in Sudan: An application of the Health Belief Model

Abstract: BackgroundCorona virus disease (covid-19) is an emerging highly infectious disease caused by novel corona virus (SARS-CoV-2). Several public health and social protective measures that may prevent or slow down the transmission of the COVID-19 were introduced. However, these measures are unfortunately neglected or deliberately ignored by some individuals.ObjectiveTo identify the factors influencing intention to adhere to precautionary measures againstCOVID-19 in Sudan.Methods and DesignCross sectional online bas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Such finding is linear with a previous study which found that self-efficacy was the main factor that encourage pregnant women compliance with the preventive behavior (Mo et al, 2021). It is also supported by a study conducted by Mehanna, E, & L.P (2021) which revealed that women's self-efficacy was strongly correlated with compliance with COVID-19 preventive behavior. When individuals are more confident in their ability to take preventive action, the more likely they would carry out the behavior.…”
Section: Discussionsupporting
confidence: 87%
“…Such finding is linear with a previous study which found that self-efficacy was the main factor that encourage pregnant women compliance with the preventive behavior (Mo et al, 2021). It is also supported by a study conducted by Mehanna, E, & L.P (2021) which revealed that women's self-efficacy was strongly correlated with compliance with COVID-19 preventive behavior. When individuals are more confident in their ability to take preventive action, the more likely they would carry out the behavior.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with past findings concluding that perceived benefits are most often associated with predictors of adherence to health behaviors, and that the "threat" constructs of severity and susceptibility do not consistently predict behaviors. 4,5,7,8,9,10,14 For instance, application of the HBM framework to predict intent to receive and pay for a COVID-19 vaccine in Malaysia found that high perceptions susceptibility and perceived benefits of receiving a vaccine were associated with increased intent. 4 However, while intent to use a contact tracing app in Belgium was also significantly associated with perceived benefits of the app, it was not significantly associated with either of the "threat" constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the critical need for research predicting health behaviors to reduce transmission during this time, there has been very little literature published to date that seeks to understand the relationship between social, psychological, and motivational factors predicting social distancing compliance in the U.S. Several international studies have sought to examine these constructs using the Health Belief Model (HBM), but very few have involved a U.S. population. 3,4,5,6,7,8,9,10 Due to the https://doi.org/10.1017/dmp.2021.262 concerning rates of infection and mortality in the United States, research examining factors contributing to adherence or disregard for disease prevention strategies like social distancing is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Mehanna et al [10] argued that while COVID-19 infection-control guidelines can slow and prevent disease spread and transmission, the deliberate or accidental disregard of guidelines by some individuals can lead to the disease spreading rapidly.…”
mentioning
confidence: 99%